Spontaneous Coronary Artery Dissection - Daniela Crousillat, MD; Amy Sarma, MD; Malissa Wood, MD; Sahar Naderi, MD, MHS; Katherine Leon, MS; C Michael Gibson, MD; Aaron Aday, MD, MSc; Anna Grodzinsky, MD, MS; Kathy Izard, BA; Jason C. Kovacic, MD, PhD; Mark E. Lindsay, MD, PhD; Dermot Phelan, MD, PhD; et al. (JACC: Advances)
Despite marked advancements in the recognition and diagnosis of spontaneous coronary artery dissection (SCAD) over the past decade, knowledge of the basic pathophysiologic mechanisms of disease, contributing factors, and treatment continue to be poorly understood. We describe significant research gaps in our knowledge of SCAD and introduce strategies including the role of patient advocacy, independent registries, and creation of diverse centers of excellence to bridge the gap in clinical care, research, and outcomes. Lastly, we introduce an innovative patient-centered clinical care and research framework established through the SCAD Alliance and International Spontaneous Coronary Artery Dissection registry as a model for advancing knowledge of SCAD.